Implications of The Revision of Law No. 16 of 2019 Againts the Practice of Child Marriage - Iswandi, Iswandi; Yaqub, Andi (Al-'Adl, 2023)
After the revision of Law No. 16 of 2019 concerning Marriage has implications for increasing child marriage by setting the age of 19 for women. The purpose of this study is to evaluate the existence of Law no. 16 of 2019 regarding the standardization of the age for child marriage. This type of literature exploration research with data collection is based on BPS census data from 2017-2020. The results of this study show that the practice of child marriage after the Marriage Law 2017 age <16 reached 16% and in 2018 dropped to 10%. However, in 2019 the age <16 increased by 14% and the age 17-18 was 23%, while in 2020 the age <16 increased to 15% and the age 17-18 decreased to 19%. The marriage presentation shows that due to the facto revision of the UUP it cannot minimize the practice of child marriage so it requires evaluation and consideration of the content of Law No. 16 of 2019 concerning Marriage.